Evaluation of the Tobacco Treatment Program of the brazilian Unified Health System in a municipality in the southwest of Minas Gerais (Research, Society and Development, 2021)
Introduction: In the 1980s, the first measures against smoking were taken by the Brazilian Ministry of Health. As of 2002, the Smoking Treatment Program (STP) was implemented in the Unified Health System (UHS), providing free treatment at the Family Health Strategies (FHS). Objectives: To evaluate and describe the PTT, applied to its users in a city in the southwest region of Minas Gerais, as well as to outline the sociodemographic profile of these individuals. Materials and methods: This is an observational, cross-sectional study with a quantitative and qualitative approach, whose data collection took place between March 2019 and March 2020 through the application of a systematic questionnaire to the professionals of the target ESFs and 52 users of the PTT enrolled in the program. Results: It was observed that most patients were female and that 68% were successful in smoking cessation after their submission to STP, with group therapy being evaluated by users as the best treatment. A significant association (p